PUBLIC COMMUNICATION MODEL OF THE SIDOARJO REGENCY GOVERNMENT IN FACING THE NEW NORMAL COVID-19 - Didik Hariyanto; Ferry Adhi Dharma; Hendra Sukmana (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2021)
Changing the policy from Large-Scale Social Restrictions (PSBB) to the “new normal” policy during the Covid-19 pandemic requires effective and targeted public communication. Therefore, this study aims to analyze and describe the implementation of the Crisis and Emergency Risk Communication (CERC) model in the public communication of the Sidoarjo Regency government during the new normal period in the Covid-19 pandemic. The method used in this research is a qualitative study, with data sources from interviews analyzed using the CERC model. The results showed that the Sidoarjo Regency government's public communication was mainly done through social media, websites, and outdoor-indoor publications in the form of banners. However, this public communication model is not by the needs of the heterogeneous Sidoarjo community, especially with the unequal distribution of media literacy. Thus, the necessary public communication is through community participation with two-way communication channels, persuasive interpersonal communication, as well as group and organizational communication, in accordance with the CERC model.